Actors, the Actor Network and Their Impact on Public Space Management: Social Network Analysis as a Method - Lee, Dahae (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Public space is an essential element of cities as it offers several benefits. Due to its significance, there is much discussion of its design, development and use. Although equally important, the management of public space lacks attention in academia and policy. This is regrettable given concerns about the quality of public space and calls for substantial changes in public space management. Moreover, while multi-actor involvement in public space management has become popular, its impact has been less studied. This paper attempts to fill the research gap by presenting an empirical study on Görlitzer Park in Berlin, Germany. Thereby, it focuses on multi-actor involvement in public space management. Based on the results of social network analysis, the paper provides a valuable insight into the actors involved, the actor network and their impact on public space management. Most importantly, the paper argues that the structure of the actor network matters for managing public space. This suggests that improving the actor network can be a key to enhancing the quality of public space. The paper also discusses how to improve communication between actors to better manage public space.
Keywords: Public space management; park management; social network analysis; network theory